CLOSING STRATEGIES CONVEYED BY THE ENGLISH TEACHERS - Rachmawati Rachmawati; Nurul Fitri; Hustarna Hustarna (International Conference on Languages and Arts, 2014)
The present research is inevitable at revealing the types of closing strategies and the reasons of realizing those closing strategies by the teachers at one of private English courses in the Jambi City. Two English teachers engage in the research who coach students at the advanced and conversation classes. The data of the research are utterances produced by the research subjects (teachers) all through the classroom interactions. The utterances are assembled by means of a tape recorder and a pen-cam as the supporting instrument. Every single word is recorded by these two instruments (a tape recorder and a pen cam) conversely not all of the utterances are regarded as the data (data reduction process). Besides the two instruments mentioned, note-taking is too utilized in an attempt to get rid of bias of the research. The results of this research highlights nine genuses of closing strategies uttered by the research subjects, namely positive comment (31 occurrences), excuse (12 occurrences), imperative to end (27 occurrences), blame (5 occurrences), goal (40 occurrences), summary (70 occurrences), an expression of thanks for the conversation (15 occurrences), plan (16 occurrences), and general wish (5 occurrences). Briefly, the cultural issue entirely have a consequence on the closing strategies realized by the research subjects.   Keywords: closing utterances, politeness, strategies